1995
DOI: 10.1207/s15327655jchn1201_3
|View full text |Cite
|
Sign up to set email alerts
|

Young Women's Breast Self-Examination Knowledge and Practice

Abstract: A descriptive survey was conducted to identify and describe breast self-examination (BSE) knowledge and practices of young women (< 45 years). The sample consisted of 65 female university nursing students, whose ages ranged between 17 and 45 years (M = 19). Data were collected using a self-administered questionnaire and analyzed using descriptive statistics. The results of the study were that 99% of the sample had performed BSE in the previous 12 months. Fewer than half (44%) of these participants indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
6
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
6
29
6
3
Order By: Relevance
“…Also, the low percentage of nurses performing monthly BSE is similar to the findings of other studies (Cole & Gorman, 1984;Edgar et al, 1984). The main reason identified for not performing BSE, namely "forgetfulness," has been a common finding among nurses (Budden, 1995;Cole & Gorman, 1984). This issue requires further consideration by health educators to identify strategies that remind and prompt women to regularly perform BSE.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also, the low percentage of nurses performing monthly BSE is similar to the findings of other studies (Cole & Gorman, 1984;Edgar et al, 1984). The main reason identified for not performing BSE, namely "forgetfulness," has been a common finding among nurses (Budden, 1995;Cole & Gorman, 1984). This issue requires further consideration by health educators to identify strategies that remind and prompt women to regularly perform BSE.…”
Section: Discussionsupporting
confidence: 86%
“…Nurses have given many reasons for their BSE nonperformance such as "not having enough time," "not thinking about the possibility of breast cancer," and "forgetfulness" (Bayley, Checkroom, Fain, &Wilson, 1980). These reasons have also been given by student nurses for their BSE nonperformance (Budden, 1995). However, the results of the early Australian study conducted by Bayley et al (1 980) must be viewed with caution because of the small convenience sample used (N = 47).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is lower than the 77% obtained among university nursing students in the USA, who correctly identi ed the recommended time (12).…”
Section: Discussioncontrasting
confidence: 69%
“…Findings from this study further showed that almost half (48%) of the respondent had negative attitude towards breast self examination, this is however, contrary to [10,14] who reported that respondents had a healthy attitude to breast cancer screening.…”
Section: Discussioncontrasting
confidence: 80%